Continuity in crime: Sex and age differences - Andersson, Jan (Journal of quantitative criminology, 1990)
This study deals primarily with the question of continuity in serious criminality. The study follows a cohort consisting of 15,117 individuals from the age of 15 years through the age of 30 years. The age-based transition probabilities are studied, both for males and for females, showing that the transitions for females conform to a first-order Markov chain, so that the original matrices can be seen as estimates from a single “parent matrix.” This was not the case for males. The predictive power of prior criminality for later transition probabilities is also studied. Finally, the difference between stating that a given percentage will relapse in crime and the ability to make real prediction is emphasized.